2019
DOI: 10.5324/nje.v28i1-2.3055
|View full text |Cite
|
Sign up to set email alerts
|

Do young people who are not in education, employment or training (NEET) have more health problems than their peers? A cross-sectional study among Norwegian adolescents

Abstract: Objectives: An increasing proportion of young Norwegians are categorised as too ill to attend upper secondary education, and poor physical and mental health may reduce their opportunities to return to school or find paid employment. This study examined the differences in self-perceived health, mental health, and prevalence of pain between Norwegian adolescents, who are not in education, employment or training (NEET) compared to adolescents who attend upper secondary school (age 16-21 years).Design: Cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The difficulties related to school-to-work transition generally seem to lead to youth psychological distress, anxiety, and maladaptive behavior (Parola et al, 2019;Stea et al, 2019) that might eventually contribute to their low life satisfaction and poor mental health (Forma et al, 2017;Kivijärvi et al, 2019). Cao et al (2020) suggested that young people may be at the highest risk for mental illnesses due to the COVID-19, regardless of their experience with the novel coronavirus.…”
mentioning
confidence: 99%
“…The difficulties related to school-to-work transition generally seem to lead to youth psychological distress, anxiety, and maladaptive behavior (Parola et al, 2019;Stea et al, 2019) that might eventually contribute to their low life satisfaction and poor mental health (Forma et al, 2017;Kivijärvi et al, 2019). Cao et al (2020) suggested that young people may be at the highest risk for mental illnesses due to the COVID-19, regardless of their experience with the novel coronavirus.…”
mentioning
confidence: 99%
“…Six studies conducted gender-stratified analysis [ 19 , 20 , 42 , 46 , 49 , 50 ]. In Bania et al [ 42 ], conduct problems at age 15–16 predicted becoming NEET 9 years later among men (OR 1.17, CI 1.07–1.28) and women (OR 1.25, CI 1.17–1.33), while emotional problems were associated with lower odds of becoming NEET in men (OR 0.88, CI 0.81–0.97), but not women (OR 1.04, CI 0.97–1.11).…”
Section: Resultsmentioning
confidence: 99%
“…In their cross-sectional study, Stea et al [ 50 ] found an association between NEET and psychological distress among women (OR 2.40, CI 1.00–5.20), but not men (estimate unavailable), whereas Basta et al [ 46 ] found no association with distress among women (OR 0.98, CI 0.95–1.02) and men (OR 0.99, CI 0.96–1.03).…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantaged situation of NEET youth is further exacerbated by health problems (OECD 2015b;Hammarström and Ahlgren 2019;Stea et al 2019) and gender (Russell 2016 a,b;Saczyńska-Sokół 2018). Therefore, NEET youth require a complex, multi-faceted approach since gender, place of residence, manner of intervention, possible financial support, disability, and other temporal factors can all significantly impact upon whether young people are in employment or education (Luthra et al 2018).…”
Section: Reasons and Solutions For Neet Statusmentioning
confidence: 99%